2018
DOI: 10.3390/biom8030062
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Molybdenum Polyoxometalated Compound to Increase the Amount of Extractives from Wood Wastes

Abstract: The treatment of wood wastes of Castanea sativa L., Quercus frainetto, Larix decidua, and Paulownia tomentosa S. in autoclave in the presence of micrometric crystals of H3PMo12O40 showed an impressive increase of the amount of extractives. The extractives were mainly constituted of insoluble compounds that were analyzed by using gas chromatography-mass spectrometry (GC-MS) after acetylation. The GC-MS analysis of the chloroform soluble fraction of the extractives obtained from sativa showed the presence of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…These studies show that heat modification and the use of molybdenum catalysts increase fatty acid esters (which have possible use in biodiesel synthesis) and that an increased amount of carbohydrates allows obtaining valuable amounts of biologically active compounds [16,17].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…These studies show that heat modification and the use of molybdenum catalysts increase fatty acid esters (which have possible use in biodiesel synthesis) and that an increased amount of carbohydrates allows obtaining valuable amounts of biologically active compounds [16,17].…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have shown that the water extraction procedure made it possible to obtain mainly water-soluble compounds while non-polar or less polar lipophilic compounds cannot be extracted using this procedure [16].…”
Section: Introductionmentioning
confidence: 99%
“…P. tomentosa extract was obtained by the treatment of wood wastes in an autoclave, in the presence of micrometric crystals of H3PMo12O40, according to the method previously described [28] .…”
Section: Introductionmentioning
confidence: 99%